Features of the sonographic picture in female veterans of reproductive age who suffered injuries during combat actions - Serbeniuk, A.V. (Reproductive health of woman (Online), 2022)
The objective: to study the features of the sonographic picture of the pelvic organs in women of reproductive age who took part in combat operations and suffered a concussion. Materials and methods. Ultrasound examination of the pelvic organs with Doppler study on the 5th and 21st days of the menstrual cycle was performed in 457 women of reproductive age who took part in combat operations and suffered a concussion. 246 patients of theses persons with a history of trauma without post-concussion syndrome were included in the comparison group, 211 women with consequences of concussion in the form of post-concussion syndrome – in the main group. The control group included 30 healthy civilian women of reproductive age. The concentration of progesterone in blood serum was studied in all subjects on the 5th and 21st days of the menstrual cycle. The average age of women was 37.08±4.23 years. The period of stay in the combat zone was 60.26±42.21 months, the time since the traumatic brain injury (concussion) was 18.8±9.2 months. Results. In patients of the main group without hyperplastic processes of the endometrium the M-echo thickness on the 21st day of the menstrual cycle was 1.12 times less (p<0.001) than in the control group, and 1.15 times less in patients in the comparison group (p<0.001). In 20.71 % of women with a contusion during combat operations, there is an inferior secretory transformation of the endometrium with increased echogenicity only in the peripheral parts of the M-echo with a hypoechoic zone in the center, in 13.81 % of patients there are no secretory changes in the endometrium on echograms, which manifested by the preservation on the 21st day of its three-layer construction, typical for the preovulatory period, with a hypoechoic functional layer. Intrauterine synechiae are formed in 10.95 % of women who suffered contusions during combat operationss, hyperplastic endometrial processes – 30.24 % of women, 12.3 8% of which had hyperplasia, 17.86 % –endometrial polyps.In patients who suffered a contusion during combat operations a decrease in the vascularization of the corpus luteum with a significant increase in the resistance index of blood flow in the corpus luteum by 1.27 times and a decrease in the maximum systolic velocity by 1.19 times was, in the subjects of the main group compared to women of the comparison group – 1.07 (p<0.01) and 1.05 (p<0.01) times, respectively. On the 21st day of the menstrual cycle in women who took part in combat operations and had concussion, a correlation between the level of serum progesterone and the index of blood flow resistance in the corpus luteum – r=-0.76, p<0.05, as well as maximum systolic blood flow velocity - r=0.70, p<0.05 was established. Conclusions. According to the ultrasound examination of the pelvic organs for women of reproductive age who took part in combat operations and suffered a concussion, ultrasound changes in the structure of the tissues of the pelvic organs and their vascularization are typical, in particular, the thickening of the M-echo on the 21st day of the menstrual cycle, and in a third of cases – the presence of hyperplastic changes of the endometrium. Мета дослідження: вивчення особливостей сонографічної картини органів малого таза у жінок репродуктивного віку, які брали участь у бойових діях та зазнали контузії. Матеріали та методи. Ультразвукове дослідження органів малого таза із допплерометрією на 5-й та 21-й дні менструального циклу проведено у 457 жінок репродуктивного віку, які брали участь у бойових діях та зазнали контузії. З них 246 пацієнток з травмою в анамнезі без постконтузійного синдрому увійшли до групи порівняння, 211 жінок із наслідками контузії у формі постконтузійного синдрому – до основної групи. До контрольної групи включено 30 умовно здорових цивільний жінок репродуктивного віку. Концентрацію прогестерону у сироватці крові досліджували у всіх обстежених на 5-й та 21-й дні менструального циклу. Середній вік жінок становив 37,08±4,23 року. Термін перебування у зоні бойових дій становив 60,26±42,21 місяця, час з моменту отримання травматичного пошкодження мозку (контузії) – 18,8±9,2 місяця.Результати. У пацієнток основної групи без наявності гіперпластичних процесів ендометрія товщина М-ехо на 21-й день менструального циклу була меншою в 1,12 раза (p<0,001) стосовно осіб контрольної групи, щодо пацієнток групи порівняння – в 1,15 раза (p<0,001). У 20,71 % жінок, які зазнали контузії під час бойових дій, спостерігається неповноцінна секреторна трансформація ендометрія з підвищенням ехогенності тільки у периферійних відділах М-ехо з гіпоехогенною зоною у центрі, у 13,81 % пацієнток секреторні зміни ендометрія на ехограмах відсутні, що проявляється збереженням на 21-й день його тришарової будови, типової для передовуляційного періоду, з гіпоехогенним функціональним шаром. Внутрішньоматкові синехії формуються у 10,95 % жінок, які зазнали контузії під час бойових дій, гіперпластичні процеси ендометрія – у 30,24 % жінок, з яких у 12,38 % – гіперплазія, у 17,86 % – поліп ендометрія. У пацієнток, які зазнали контузії під час бойових дій, встановлено зниження васкуляризації жовтого тіла з достовірним підвищенням індексу резистентності кровотоку у жовтому тілі в 1,27 раза та зниженням максимальної систолічної швидкості в 1,19 раза, в осіб основної групи порівняно з жінками групи порівняння – в 1,07 (p<0,01) і в 1,05 (p<0,01) раза відповідно. На 21-й день менструального циклу у жінок, які брали участь у бойових діях та зазнали контузії, встановлено кореляційну залежність між рівнем сироваткового прогестерону та індексом резистентності кровотоку у жовтому тілі – r=-0,76, р<0,05, а також максимальною систолічною швидкістю кровотоку – r=0,70, р<0,05.Висновки. За даними ультразвукового обстеження органів малого таза для жінок репродуктивного віку, які брали участь у бойових діях та зазнали контузії, характерними є ультразвукові зміни структури тканин органів малого таза та їхньої васкуляризації, зокрема, потовщення М-ехо на 21-й день менструального циклу, а в третині випадків – наявність гіперпластичних змін ендометрія.